Alkali treatment on nettle fibers: Part I: investigation of chemical, structural, physical, and mechanical characteristics of alkali-treated nettle fibers. Issue 8 (3rd August 2017) - Kumar, Navdeep; Das, Dipayan
Abstract: This work deals with alkali treatment on nettle fibers. The first part of this work examines structure and properties of alkali-treated nettle fibers, while the second part reports on optimization of alkali treatment to improve tensile properties of nettle fibers. In this part, the alkali-treated nettle fibers were examined for their chemical, structural, physical, and mechanical characteristics and compared to untreated fibers. The alkali treatment appeared to remove lignin from the fiber, thereby resulting in increase in its crystallinity, improvement in its appearance, and decrease in its width and linear density. The untreated fiber was quite strong but less flexible and less extensible. A mild alkali treatment resulted in increase in tensile strength and elongation at break, without much changing initial modulus. On the other hand, a severe alkali treatment resulted in reduction in fiber strength as well as initial modulus without much change in elongation at break.